Exciton dissociation in correlated molecular photocells. (May 2021) - Sánchez, Fernando; Amador-Bedolla, Carlos; Sánchez, Vicenta; Wang, Chumin
Abstract: Electron-hole separation is a crucial process for the photocurrent generation in organic solar cells, where the interaction of molecular photocells and its influence on the energy conversion efficiency are studied by means of an attractive Hubbard model on an excitonic-state lattice, whose impurity sites originated from the local electron-hole interaction inhibit a reciprocal-space analysis. Alternatively, an independent channel transformation followed by a real-space renormalization approach were used to address a large lattice of excitonic states. The results show a remarkable growth of the quantum efficiency (Q) when a charge transfer between photocells is considered, and such high Q remains even in the strong electron-hole interaction region. The calculation of Q is based on the local density of states at such impurity sites, whose third and fourth spectral moments have been analytically confirmed. Finally, this study suggests an optimal distance between photocells to achieve high Q in accordance with experimental results. Highlights: Coarse grain quantum model of interacting molecular photocells. Exciton diffusion and dissociation in organic solar cells. Multidimensional lattice of excitonic states with impurity sites. Independent channel plus real-space renormalization method. Optimal separation between photocells for high quantum efficiency.